ARTIFICIAL INTELLIGENCE (AI) OPTIMALIZATION IN CUSTOMER BEHAVIOR ANALYSIS TO DETERMINE MARKETING STRATEGIES: SYSTEMATIC LITERATURE REVIEW - Prameswari, Amanda Tiara; Pebrianggara, Alshaf; Yulianto, Mochamad Rizal; Almanfaluti, Istian Kriya (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This research aims to examine the optimization of the use of AI in understanding and analyzing customer behavior in developing effective and efficient marketing strategies. Method: The method used in this research is the SLR (Systematic Literature Review) method, by collecting data through various sources of academic database articles such as Google Scholar, IEEE Xplore, Science Direct and others that discuss the application of AI. Results: The results of this literature review show that the application of AI such as machine learning and data analysis is able to identify customer preferences and needs, which will be used by companies in designing more personalized and efficient marketing strategies. Novelty: In the digital era, the use of artificial intelligence (AI) in customer behavior analysis has become one of the effective tools to determine a more appropriate marketing strategy. Optimizing AI through the SLR method is an important step for companies in achieving a competitive advantage in understanding customer behavior patterns more accurately in a dynamic market.